FATIGUE LIFE OF TUBULAR PROFILE ALUMINUM ALLOY 6013-T6 - Cornelis Voorwald, Herman Jacobus [UNESP]; Tonoli, Cesar Salvarani [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Gomes, JFS; Meguid, S. A. (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2016)
The fork suspension's steerer tube in a bicycle is a component of great importance considering that dynamic loading during operation may cause accident to the rider. This component is manufactured by machining processes from aluminum alloy 6013-T6 extrusion tubular profile. The objective of the present paper is to study the effect of different shot peening conditions on the fatigue behavior of the material and, as a consequence, increases in the useful life/safety of the structure. Experimental results showed that thread forming by manufacturing process increased the fatigue strength of the aluminum alloy, in comparison to the manufacturing process through conventional machining.
Keywords: Bicycle; residual stresses; steerer; fork suspension